The adventures of Tom Sawyer - Twain, Mark, 1835-1910. (New York, NY Scholastic Inc., 1999)
The adventures and pranks of a mischievous boy growing up in a Mississippi River town in the early nineteeenth century.
G8
Keywords: Sawyer, Tom (Fictitious character) -- Fiction; Runaway children -- Fiction; Child witnesses -- Fiction; Male friendship -- Fiction; Boys -- Fiction; Mississippi River Valley -- Fiction; Missouri -- Fiction; Adventure stories; Humorous stories